PROSPECT OF ZEOLITE APPLICATION IN AGRICULTURE - Suwardi, Suwardi (Jurnal Zeolit Indonesia, 2002)
Although zeolites have been known since the 50s the application of zeolites in Indonesia started in the 80s after promotion by the Mineral Technology Research Centre. Before that period, zeolites were only used as construction materials for wall decoration. Zeolites became popular after publication of zeolite research into many aspects of possible applications. Applications of zeolites are based on their characteristics. Initially natural zeolites were used as fillers in the paper industry, ion exchangers in water treatment, separation of nitrogen and oxygen, sorbents in drying, and construction materials. At the same time, applications of zeolites were developed as feed additives for animals and for water treatment in shrimp ponds. In some countries, zeolites have been used as industrial materials, improvement of agricultural production, and environmental protection. In agriculture, applications of zeolites can be used directly to soils as materials for growth media, mixed with manures during decomposition process, and for mixing with urea as slow release agent. The number of zeolite factories in Indonesia is still low and they produce zeolites in powder and grain forms. In recent years, some zeolite factories have been built to produce zeolites for material of industry, agriculture and environmental protection. The most important effort for zeolite factories is how to produce high quality of zeolite. The prospect of zeolite applications in agriculture is very good as (1) soil amelioration for low cation exchange capacity of soils, (2) material for mixing with fertilizer, (3) material as growth media for horticulture and seedling plantation plants, (4) material for improvement of compost quality, (5) material for water treatment of fish ponds, (6) food additives for animals.